EFEKTIVITAS PENEGAKAN HUKUM LINGKUNGAN DALAM MENGATASI KRISIS LINGKUNGAN HIDUP DI INDONESIA - Rahil Khalisa; Saskia Besthianna; Shofa Zahira Arrumaisha; Silviana Cindy Kharissa; Syavina Alya Rohimah (STID Raudlatul Iman Sumenep, 2025)
The